Hemoglobin Levels and Red Blood Cells Distribution Width Highlights Glioblastoma Patients Subgroup With Improved Median Overall Survival - Kaisman-Elbaz, Tehila; Elbaz, Yonatan; Merkin, Vladimir; Dym, Lianne; Noy, Ariel; Atar-Vardi, Maya; Bari, Romi; Turiel, Sivan; Alt, Adi; Zamed, Tali; Eskira, Yael; Lavrenkov, Konstantin; et al. (Frontiers in Oncology, 2020)
Glioblastoma multiforme (GBM) is known for its dismal prognosis, though its dependency on patients' readily available RBCs parameters is not fully established. In this work, 170 GBM patients, diagnosed and treated in Soroka University Medical Center (SUMC) in the last 12 years were retrospectively inspected for their survival dependency on pre-operative RBCs parameters. Beside KPS and tumor resection supplemented by oncological treatment, age<70 (HR=0.4, 95% CI 0.24-0.65, p=0.00073), low hemoglobin level (HR=1.79, 95% CI 1.06-2.99, p=0.031) and Red Cell Distribution Width (RDW)<14% (HR=0.57, 95% CI 0.37-0.88, p=0.018) were found to be prognostic to patients’ overall survival in multivariate analysis, accounting for false discovery rate of less than 5% due to the multiple hypothesis testing. According to these results, a stratification tree was made, which favorable route highlighted a subgroup of nearly 30% of the cohort's patients whose median overall survival was 21.1 months (95% CI 16.2-27.2) - higher than the average Stupp protocol overall median survival of about 15 months. A discussion on the beneficial or detrimental effect of RBCs parameters on GBM prognosis and its possible causes is given.